2007
DOI: 10.5216/rpt.v24i1.19880
|View full text |Cite
|
Sign up to set email alerts
|

INFLUÊNCIA DA TEMPERATURA NA BIOLOGIA DE TRIATOMÍNEOS.XX. Triatoma maculata (ERICHSON, 1848) (HEMIPTERA, REDUVIIDAE)

Abstract: Estudou-se o efeito da temperatura no ciclo evolutivo de Triatoma maculata {Erichson, 1848) para estabelecer a sua influência no desenvolvimento do triatomineo, conhecer alguns aspectos de sua biologia c dominar técnicas de criação para viabilizar o uso dessa espécie nos testes experimentais em doença de Chagas. O período médio de incubação dos ovos de T.maculata, para machos e fêmeas, foi de 29 e de 16 dias, à temperatura de 25° e 30°C, respectivamente.A temperatura de 25°C, a duração média do ciclo evolutivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
1
5
1
3
Order By: Relevance
“…Under these conditions, the average developmental period was 180.1 days. Our result was closed to that reported by Silva (1985) at 25 o C (159-170 days).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Under these conditions, the average developmental period was 180.1 days. Our result was closed to that reported by Silva (1985) at 25 o C (159-170 days).…”
Section: Resultscontrasting
confidence: 61%
“…Thus, the low sampling obtained made it difficult to infer about the averages of elapsed time between the feeding and defecation from the third feeding on (Table III). Silva (1985) conducted studies on the intermoulting period of T. rubrovaria, by offering bird blood (Gallus gallus) as food source at temperatures of 25ºC and 30ºC. In our study, Mus musculus was utilized as the food source, and the insects were kept under environmental conditions of Rio de Janeiro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Feliciangeli and Rabinovich (1985) observed an average of 19.1 days of incubation for T. maculata eggs, which is similar to our results, in which average incubation time was 18.1 days. Silva et al (1995), by studying the influence of temperature on the development of T. maculata blood fed on chicken, verified a difference in the egg incubation period: 29 and 16 days at 25 and 30°C, respectively. Luitgards-Moura et al (2005) have also shown that higher temperatures diminish the incubation period; with temperatures ranging from 21.5 to 32°C (average 27.6°C) and weekly blood feeding on mice, these authors reported a variation in the period of egg incubation between 14 and 42 days, with a significant negative correlation between temperature and incubation time (-0.98).…”
Section: Discussionmentioning
confidence: 99%
“…Los tiempos de los estadios encontrados aumentaron progresivamente desde el estadio I hasta el estadio V, lo que concuerda con lo reportado para T. maculata (25)(26)(27)(28) y para otras especies del género Triatoma alimentadas con otras fuentes sanguíneas (29).…”
Section: Hd-hpdunclassified
“…Con respecto a la fecundidad, en este trabajo se encontró que una hembra produce, en promedio, 27,70 huevos en un tiempo promedio de 32,74 días, valores menores a los conseguidos en trabajos previos (25)(26)(27)(28), los cuales coinciden en reportar fecundidades en el orden de las centenas de huevos por hembra en un tiempo promedio que varía entre 60 y más de 200 días. En resumen, podríamos decir que la alimentación de T. maculata con sangre humana supone una condición adversa a esta especie, dada la alta mortalidad en los estadios de ninfa; la mayor mortalidad (77,78%) y el menor porcentaje de muda (22,23%) se encuentran en el estadio V, es decir, la proporción de individuos que alcanzan el estado adulto es reducido, lo que desfavorecería el mantenimiento de una colonia de T. maculata cuando se alimenta con sangre humana, más aún si consideramos los valores bajos de fecundidad y longevidad de las hembras.…”
Section: Hd-hpdunclassified